2021
DOI: 10.31548/ujvs2021.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Intake and Distribution in the Body of Broiler Chickens With Ornithobacteriosis

Abstract: The clinical efficiency of the an bio c is determined by its distribu on in organs and ssues, the ability to penetrate the physiological and pathological barriers of the body. The ar cle presents the results from a study of the intake, distribu on, and excre on of doxycycline hyclate -the ac ve substance of the an bio c pollodoxin from the body of broiler chickens (the Cobb-500 cross) with ornithobacteriosis.It has been established that 24 hours a er the pollodoxin solu on applica on in broiler chickens with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Vitamin D plays a significant role in the metabolism of calcium and phosphorus in the body of animals. It is necessary for the assimilation of minerals from milk and feed, regulation of osteosynthesis, osteogenesis, embryonic development, and other vital processes (Vlizlo et al, 2007;Tyshkivska, 2008;Nelson et al, 2016). Lack of Vitamin D is one of the reasons for the increase in the death of young cattle and a decrease in productivity (Goff, 2008;Dittmer & Thompson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D plays a significant role in the metabolism of calcium and phosphorus in the body of animals. It is necessary for the assimilation of minerals from milk and feed, regulation of osteosynthesis, osteogenesis, embryonic development, and other vital processes (Vlizlo et al, 2007;Tyshkivska, 2008;Nelson et al, 2016). Lack of Vitamin D is one of the reasons for the increase in the death of young cattle and a decrease in productivity (Goff, 2008;Dittmer & Thompson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that viral diseases are the most common in industrial poultry farms ( Haji-Abdolvahab et al, 2019 ; Vishchur et al , 2020 ; Dukhnitskyi and Tyshkivska, 2021 ). A review article by Ike et al (2021) also focuses on significant economic losses in broiler and egg flocks due to the development of Newcastle disease (ND) and infectious bronchitis (IB) due to the significant mortality of young birds and increased losses during rearing.…”
Section: Introductionmentioning
confidence: 99%